GROWTH AND YIELD OF JATROPHA PLANTS IN RESPONSE TO MICRONUTRIENTS SUPPLY - BOTARO, Fernando Grandizoli; FURLANI JÚNIOR, Enes; FERRARI, Samuel; SANTOS, Danilo Marcelo Aires dos (Revista Brasileira de Engenharia de Biossistemas, 2013)
This study aimed to evaluate the effect of boron, zinc, copper and molybdenum supply on yield and growth of Jatropha curcas plants growing in Cerrado’s region. The experimental design consisted of 4 levels of boron (0, 0.25, 0.5 and 1.0 kg ha-1); 4 levels of zinc (0, 0.5, 1.0 and 2.0 kg ha-1); 4 levels of copper (0, 0.4, 0.8 and 1.6 kg ha-1) and 4 levels of molybdenum (0, 0.15, 0.3 and 0.6 kg ha-1) applied on top dress of Jatropha plants. The evaluation of plant height, stem diameter, number of branches and inflorescences were monthly measured from January to April 2011. The yield of Jatropha curcas was obtained by collecting the seeds during the period from March to May 2011. The application of boron, zinc and copper showed no effect on growth parameters and yield of Jatropha plants during the second year growing season in Cerrado’s area. In addiction, molybdenum fertilizer application decreased the number of inflorescences per plant, increased stem diameter and number of branches per plant showing no effect on yield of young Jatropha plants. These results suggest that there is no need to apply micronutrients on young plants in Jatropha orchards.